Organizational and technological implications of cognitive machines designing future information management systems - Nobre, Farley Simon, 1971-; Tobias, Andrew M.; Walker, David S. (David Stanley), 1941-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book addresses the possible implications of cognitive machines for current and future organizations"--Provided by publisher.
Section VII: General Conclusions -- 15. Contributions and Extensions -- Appendix Section -- Glossary -- About the Authors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 13, 2010).
Keywords: Knowledge management; Organizational learning; Capability maturity model (Computer software); Cognitive machine framework; Cognitive machines; Cognitive network of organizations; Computational organization management networks; Information processing theory; Methodology of organization design; Nature theory of organizations; Organization and the environment; Organizational cognition; Strategies of organization design; Electronic books